Estudo da deformação de nióbio empregando a técnica de prensagem em canais equiangulares (ECAP) - Santos, Reinan Tiago Fernandes dos (2018)
This investigated the use of equiangular channel press (ECAP) in samples of pure niobium at room temperature up to 14 passes, using the Bc route, with a matrix with intersection angle between the channels of θ = 90º and 120º, with and curvature angle Ψ = 0°. During ECAP (equal channel angular pressing) deformation a bar is pressed through a rigid matrix consisting of two channels of the same cross-section, which intersect at an angle θ. The microstructure of the deformed samples has been analyzed with the aid of optic microscopy, scanning electron microscopy and Vickers Hardness (HV). With the deformation of pure niobium through ECAP, it was possible to refine the structure and increase the hardness due to the increase of the number of passes and the type of matrix. The results indicated that deformation of the niobium with a pass in the matrices of 90 ° and 120 ° was enough to produce the refinement of the microstructure and practically double the hardness values in relation to the material without deformation. The maximum microstructural refinement, steady state, occurred with 8 passes in the 120 ° matrix and 6 passes in the 90 ° matrix, indicating a higher deformation severity of the last matrix. The microstructures analyzed by scanning electron and optical microscopes revealed the microstructural changes with the increase of the number of passes and the type of matrix.